BRANDED TOURIST PRODUCT OF THE REGION ON THE EXAMPLE OF THEME GARDENS IN DOBRZYCA (Research Bulletins of the Faculty of Economic Sciences, 2021)
The article presents the social, economic and environmental benefits resulting fromthe existence of a branded touristic product in rural areas. An example of the branded tourist product are Hortulus Gardens in Dobrzyca. The article shows marketing activi-ties related to development of product and their influence on the forming of the tourism image of the Central Pomerania.
Keywords: tourist product, tourist brand, promotion, image of the region